Evaluation of the forage legume Canavalia brasiliensis CIAT 17009: An economic perspective - Junca Paredes, Jhon Jairo; Mojica Rodríguez, José Edwin; Sotelo, Mauricio E.; Burkart, Stefan (International Center for Tropical Agriculture, 2023)
In the lower tropics of the Colombian Caribbean, Bothriochloa pertusa (Colosuana) is a predominant grass species. However, during dry seasons forage production and quality drop significantly. Supplementation with legumes is an effective alternative to face this problem. Hay supplementation with the legume Canavalia brasiliensis has shown satisfying results in terms of agronomic performance and animal productivity in cattle production. This study evaluates this intervention from an economic perspective, replicating traditional farm conditions found in the region. Profitability indicators such as Net Present Value, Internal Rate of Return, Benefit-Cost Ratio, and payment period were estimated. Results show that the adoption of this technology is economically viable. The results are relevant to cattle producers since traditional production systems are deeply rooted in the region of analysis. As our study replicated a traditional production system, sustained recommendations can be made to producers to support technological change on their farms.